Comportamento ingestivo de vacas leiteiras alimentadas com silagem de milheto ou milho - do Rêgo, Aníbal Coutinho; de Oliveira, Mauro Dal Secco [UNESP]; Signoretti, Ricardo Dias; Dib, Vanessa; Almeida, Geraldo Benedito de Souza (My University, 2014)
The objective of this study was to evaluate the ingestive behavior of dairy cows fed corn and millet silage with a 5 mm particle size without inoculant, millet silage with a 5 mm particle size with inoculant, millet silage with a 20 mm particle size without inoculant, millet silage with a 20 mm particle size with inoculant. Five cows Holstein x Gir, with approximately 100 days of lactation at the beginning of the experiment and a mean body weight of 550 kg, producing an average of 15 kg of milk per day were used. The animals were arranged in a randomized 5 × 5 Latin square. The total feeding time, rumination time, chewing time, number of alimentary bolus, rumination time for bolus and number of chews was determined. The variables that make up the feeding behavior were not affected when the cows were fed different millet silages compared with corn silage. Cows fed corn silage and millet silage of 5 mm particle size had a higher intake of dry matter and neutral detergent fiber. A particle size between 5 and 20 mm, the presence or absence of inoculum and the type of silage with DM at 28%, does not affect the total feeding time, ruminating and resting of cows with an average production of 15.2 kg per day. The presence of the inoculant does not affect the intake of dry matter and neutral detergent fiber. Cows fed diets containing corn silage or pearl millet silage with a 5 mm particle size fed more DM.
Ingestive behavior of dairy cattle fed millet and corn silage
Keywords: Inoculants; Lactobacillus plantarum; Particle size; Pennisetum glaucum (L.) R. B. Propionibacterium acidipropionici